The distribution of the Bururi Long-fingered Frog (Cardioglossa cyaneospila, family Arthroleptidae), a poorly known Albertine Rift endemic - Blackburn, David C.; Boix, Christian; Greenbaum, Eli; Fabrezi, Marissa; Meirte, Danny; Plumptre, Andrew J.; Stanley, Edward L. (Zootaxa, 2016)
The species diversity of the frog genus Cardioglossa (family Arthroleptidae) is concentrated in the Lower Guinean Forest Zone of Central Africa with most of the 19 species occurring in Cameroon and neighboring countries (Amiet 1972a,b; Blackburn 2008; Hirschfeld et al. 2015). These small leaf-litter frogs are typically found in primary or secondary forest, have shrill whistling calls, are characterized by a variety of color patterns, and lay terrestrial eggs that hatch and develop into elongate, stream-adapted tadpoles (Amiet 1972a,b, 1973; Rödel et al. 2001; Hirschfeld et al. 2012). One of the most poorly known species—the Bururi Long-fingered Frog Cardioglossa cyaneospila Laurent, 1950—is also among the most geographically peripheral to the rest of the species diversity. To date, it is known only from two locations in Burundi and four in eastern Democratic Republic of Congo, regions in which armed conflicts have long hampered scientific research. In this short contribution, we (1) document both new and long unpublished records of C. cyaneospila, associate these with known museum records, and extend its geographic range, (2) highlight fruitful areas for future field surveys based on predicting an environmental envelope for this species, and (3) summarize what little is known of its natural history.